Pendugaan Kandungan Kafein Biji Kopi Liberika dengan Spektroskopi NIR Menggunakan Model Kubelka-Munk - Ei Mon Kyaw; I Wayan Budiastra; Sutrisno Sutrisno; Samsudin Samsudin; Dheni Mita Mala (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Liberica is one of coffee species that is becoming popular and increasingly in demand in present days due to its unique characteristics. Caffeine is one of the important coffee quality parameter which determines the coffee flavor, consumer preference and market price. Caffeine content is usually analyzed by chemical method which is destructive, time consuming, expensive and involving a lot of procedures. NIR Spectroscopy is one of the non-destructive techniques to overcome these disadvantages. This study was conducted at the Department of Mechanical and Biosystem Engineering, IPB University for NIR measurement and the Center of Agro-based Industry (BBIA), Bogor for chemical analysis from August to November 2019. The study aimed to determine the best calibration model for the prediction of caffeine content in Liberica coffee green bean powder. In this study, FT-NIRS in the wavelength of 1000-2500 nm was used for NIR measurement and HPLC tool was used for chemical analysis. Kubelka-Munk (K/S) and Absorbance (Log 1/R) were used as data transformation, whereas Standard Normal Variance (SNV) and Second derivative of Savitzky-Golay (dg2) as data pretreatment. In addition, Partial Least Square (PLS) and Multiple Linear Regression (MLR) were applied for multivariate calibration method. The best calibration model for the prediction of caffeine content of Liberica coffee green bean powder was obtained by the spectral data pretreated with second derivative of Savitzky-Golay (dg2) and Kubelka-Munk data transformation using PLS calibration method with the results of r = 0.90, RPD = 2.24, CV = 2.01%.